PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI DAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL ACCOUNTING DEPARTEMENT HOTEL BINTANG 5 DI KABUPATEN BADUNG - Ni Kadek Indah Sari; Komang Krishna Yogantara (Journal Research of Accounting, 2020)
This study aims to determine the variables that affect managerial performance. The independent variables used are job satisfaction (X1), organizational commitment (X2) and budget participation (X3). This research was conducted at the accounting department and manager of a 5 star hotel in Badung Regency by using purposive sampling. There is a population of 84 employees. Data analysis techniques used are data quality tests, classic assumption tests, multiple linear regression analysis and hypothesis testing. The results obtained are job satisfaction (X1) partially has a positive and significant effect on managerial performance (Y), organizational commitment (X2) partially has a positive and significant effect on managerial performance (Y) and budgetary participation (X3) partially influential positive and significant impact on managerial performance (Y).